N-myc is a key switch regulating the proliferation cycle of postnatal cerebellar granule cell progenitors - Ma, Ming (Sci Rep, 2015)
N-myc plays an important role in early cerebellar development; however, the role of N-myc in postnatal cerebellar development is still unknown. In this study, inducible and reversible N-myc mouse models (Nmyc(TRE/TRE):tTS and Nmyc(EGFP/TRE):tTS) are used to regulate and track the expression of endogenous N-myc in vivo. Loss of N-myc at the neonatal stage results in reduced proliferation of granule cell precursors (GCPs) and reduced cerebellar volume/mass. Restoration of N-myc expression no later than postnatal day 4 can rescue the cerebellar developmental defect caused by the absence of N-myc after birth. During cerebellar postnatal development, N-myc acts as a key switch, regulating the proliferation cycle of postnatal granule cell progenitors. Loss of N-myc significantly impairs the Sonic hedgehog signalling pathway, and disrupts the expression of cell cycle effectors with a significant reduction of Ccnd2. More importantly, N-myc negatively regulates the expression of microRNA-9 during postnatal cerebellar development. Our findings demonstrate that over-expression of miR-9 can inhibit the proliferation of GCPs. The regulation of these factors by N-myc is at least partly responsible for the switch role of N-myc in the proliferation cycle of GCPs.